Internalisasi Nilai-Nilai Islami dalam Materi Membangun Persatuan dalam Keberagamaan pada Mata Kuliah Pendidikan Agama Islam di Perguruan Tinggi - Nur Isra' Ahmad; Diarti Andra Ningsih (Advances In Education Journal, 2026)
Religion in Indonesia is still colored by the practice of intolerance in the academic space, so that the internalization of Islamic values in the learning of Islamic Religious Education (PAI) is an urgent need so that students are able to develop Islamic characters that are relevant to real life. This study aims to analyze the process of internalizing Islamic values in the material Building Unity in Diversity with a qualitative approach to 10 students at one of the universities in Makassar. The results of the study show that internalization takes place through the cognitive, affective, and psychomotor realms so that students not only understand the concept of diversity theoretically but also live and practice it. The manifestation of values can be seen from student behavior, while the implications of the research emphasize the importance of developing a PAI curriculum that is oriented towards the formation of Islamic character.